Ashy dermatosis: A comprehensive review - Bibush Amatya (Our Dermatology Online, 2017)
Introduction: The confusing macular hyperpigmentary disorders of uncertain aetiology include ashy dermatosis, erythema dyschromicum perstans (EDP) and lichen planus pigmentosus (LPP). They are characterized by insidious development of bluish grey macules involving the face, neck and upper trunk. The usual course of the conditions is progressive and persistent differentiating them from idiopathic eruptive macular pigmentation, which resolves in months. Materials and Methods: A comprehensive literature search was conducted in PUBMED, PUBMED CENTRAL, SCOPUS, MEDLINE, and GOOGLE SCHOLAR databases using the keywords ashy dermatosis, erythema dyschromicum perstans, lichen planus pigmentosus, acquired hyperpigmentation and facial melanosis. All the articles published irrespective of the date of publication were accessed. Results: The prevalence of ashy dermatosis is higher in Asia, Central and South America. The exact cause of ashy dermatosis is unknown but associations with contrast agents, infections and infestations have been reported. Presence of an erythematous border at the initial stage differentiates erythema dyschromicum perstans from ashy dermatosis, which lacks the initial erythematous phase. Lichen planus pigmentosus, on the other hand, may have lesions of lichen planus in other body sites with hyperpigmentation of the basal layers with or without vacuolar degeneration. The topical agents used for the treatment of these conditions have included cosmetics and camouflage, topical calcineurin inhibitors and narrow band ultraviolet therapy while the systemic agents include vitamin A capsules, clofazimine and dapsone. Conclusion: The proper diagnosis of these conditions can be aided by the use of an algorithm. A host of topical and systemic agents with variable efficacy have been used in the treatment of these conditions. No randomized controlled trials have been done till date assessing the efficacy of these agents. The isolated case reports that have assessed the use of narrow band ultraviolet therapy and topical tacrolimus ointment have shown promising results. Larger scale controlled trials are recommended to truly assess the efficacy and safety of these agents in the treatment of these hyperpigmentary disorders.